Incidence Trends for SARS-CoV-2 Alpha and Beta Variants, Finland, Spring 2021 - Kant Ravi; Nguyen Phuoc Truong; Blomqvist Soile; Erdin Mert; Alburkat Hussein; Suvanto Maija; Zakham Fathiah; Salminen Veera; Olander Viktor; Paloniemi Minna; Huhti Leena; Lehtinen Sara; et al. (CENTERS DISEASE CONTROL & PREVENTION, 2022)
Severe acute respiratory syndrome coronavirus 2 Alpha and Beta variants became dominant in Finland in spring 2021 but had diminished by summer. We used phylogenetic clustering to identify sources of spreading. We found that outbreaks were mostly seeded by a few introductions, highlighting the importance of surveillance and prevention policies.